Penerapan Model Pembelajaran Talking Stick Dalam Meningkatkan Hasil Belajar Mata Pelajaran PAI - Siskha Putri Sayekti; Zaeni Dahlan; Muhammad Fikri Al-Faruqi (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2021)
The results of observations and interviews at SDN 2 Depok show the low minimum completeness criteria (KKM) 75 scores of students in the Islamic Religious Education (PAI) subject found that student learning outcomes in the Islamic Religious Education (PAI) subject are still low, due to not focusing on learning the lack of learning methods used by the teacher. One of the contributing factors is that the learning methods used are less varied so that learning becomes monotonous. The purpose of this study was to determine the application of the talking stick method in the learning outcomes of Islamic Education. The method used is classroom action research (PTK). The object in this study was 29 students in grade V. Data collection was carried out using learning outcomes, filling out observation sheets. The data analysis used quantitative calculations which were then described in the form of presentations. Based on the learning results of the students after using the talking stick method, student learning outcomes increased each cycle. Judging from the learning outcomes of cycle 1 reached a percentage of 62% and cycle II reached 89%, meaning that there was an increase of 24%. In cycle, student learning outcomes in Islamic Education subjects have reached 62%, while in cycle II it has reached 89%. So, it can be concluded that between cycle I and cycle II an increase of 24%.